2021
DOI: 10.1007/s00192-021-04706-0
|View full text |Cite
|
Sign up to set email alerts
|

How often should ring pessaries be removed or changed in women with advanced POP? A prospective observational study

Abstract: Introduction and hypothesis This study aimed to evaluate the efficacy and safety of ring pessaries under continuous use for > 2 years. Our starting hypothesis was that their use without periodic removal, cleaning or replacement for between 24 to 48 months after insertion is safe and effective. Methods This was a prospective observational and descriptive study. One hundred one women who successfully completed the 24 first months of continuous use of a ring pessary were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Urogenital infections are common in women. Vaginal purulent discharge, pruritus, and foul smells are common among pessary users ( 33 , 34 ). In this study, with ProVate, there were no signs, or symptoms of vaginal or UTIs.…”
Section: Discussionmentioning
confidence: 99%
“…Urogenital infections are common in women. Vaginal purulent discharge, pruritus, and foul smells are common among pessary users ( 33 , 34 ). In this study, with ProVate, there were no signs, or symptoms of vaginal or UTIs.…”
Section: Discussionmentioning
confidence: 99%
“…A further prospective study has been published investigating whether rings could be left in situ for 24–48 months without removal, cleaning, or replacement. These data reported that 45 out of 93 (48.4%) had an adverse event requiring a temporary pessary break, demonstrating a further rise in “complications” with an increase in time interval [ 15 ].…”
Section: Discussionmentioning
confidence: 99%